Alat Pengontrol Kadar PH Air Dan Nutrisi Ab Mix Menggunakan Arduino Pada Sistem Hidroponik Sayur Hijau - Tri Atmaja; Abdi Pandu Kusuma (Universitas Islam Lamongan, 2020)
The world of technology today has developed quite rapidly with a lot of manufacture and development of various kinds of equipment that are able to help humans do work that is both control and automatic. One example of technological developments is automatic plant watering, smart home, automatic bird feeder, and many more. This study discusses a tool to control water pH levels and nutrients using Arduino in a green vegetable hydroponic system. The sensor used is the pH Electrode E201-C BNC sensor as a reader of pH levels in water, the TDS Meter V.1 sensor as a reader of nutrient density levels in water, and an ultrasonic sensor as a reader of water level in the reservoir to determine the volume of water so that it does not will run out. The software used is the Arduino Uno IDE. The way this tool works is that the input from the sensor will be processed by Arduino and the result is in the form of output conditioning, namely the actuator is on or not.